EFEKTIVITAS BIMBINGAN MANAJEMEN WAKTU DALAM UPAYA MENGURANGI PERILAKU PROKRASTINASI AKADEMIK SANTRI PONDOK PESANTREN INAYATULLAH YOGYAKARTA [THE EFFECTIVENESS OF TIME MANAGEMENT GUIDANCE IN AN EFFORT TO REDUCE THE BEHAVIOR OF ACADEMIC PROCRASTINATION OF SANTRI PONDOK PESANTREN INAYATULLAH YOGYAKARTA] - Saputro, Nurul Fitrian Eko; Agung, Ririh (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2022)
The purpose of this study was to determine the effectiveness of time management guidance in an effort to overcome the academic procrastination behavior of students at Pondok Pesantren Inayatullah Yogyakarta. This study uses a quantitative research method with a pre-experimental approach with a one-group pretest-posttest design. The results of the study using the Wilcoxon Signed Rank Test showed the Asymp results. Sig (2-tailed) is 0.059 0.005. This means that Ho is accepted and Ha is rejected. The conclusion of this study is that time management guidance does not reduce the academic procrastination behavior of students at the Pondok Pesantren Inayatullah Yogyakarta. However, based on the presentation, participants thought that time management could make the tasks and agenda of daily activities more organized.